Supercritical Fluid Technologies to Fabricate Proliposomes - James R. Falconer; Darren Svirskis; Ali A. Adil; Zimei Wu (Frontiers Media S.A., 2015)
Proliposomes are stable drug carrier systems designed to form liposomes upon addition of an aqueous phase. In this review, current trends in the use of supercritical fluid (SCF) technologies to prepare proliposomes are discussed. SCF methods are used in pharmaceutical research and industry to address limitations associated with conventional methods of pro/liposome fabrication. The SCF solvent methods of proliposome preparation are eco-friendly (known as green technology) and, along with the SCF anti-solvent methods, could be advantageous over conventional methods; enabling better design of particle morphology (size and shape). The major hurdles of SCF methods include poor scalability to industrial manufacturing which may result in variable particle characteristics. In the case of SCF anti-solvent methods, another hurdle is the reliance on organic solvents. However, the amount of solvent required is typically less than that used by the conventional methods. Another hurdle is that most of the SCF methods used have complicated manufacturing processes, although once the setup has been completed, SCF technologies offer a single-step process in the preparation of proliposomes compared to the multiple steps required by many other methods. Furthermore, there is limited research into how proliposomes will be converted into liposomes for the end-user, and how such a product can be prepared reproducibly in terms of vesicle size and drug loading. These hurdles must be overcome and with more research, SCF methods, especially where the SCF acts as a solvent, have the potential to offer a strong alternative to the conventional methods to prepare proliposomes.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.